Developmental trajectory of the prenatal lymphoid organs in native chickens: a macro anatomical study - Islam, Md Nabiul; Khan, Md Zahirul Islam; Jahan, Mir Rubayet; Shinoda, Koh (Asian Journal of Medical and Biological Research, 2018)
Native chickens of Bangladesh are scavenging in nature. In our previous studies, we have histologically and immunohistochemically examined the ontogeny of lymphoid organs of native chickens of Bangladesh in prenatal stages. To date, the study on gross anatomical development of prenatal lymphoid organs is lacking. In the present study, detailed macro-anatomical development of prenatal lymphoid organs of native chickens were examined during different embryonic stages of development, which was conducted in the laboratory of the department of Anatomy and Histology, Bangladesh Agricultural University. In the present study, thymus was first identified by the 10 days of incubation (ED 10) as a chain at the both side of the neck. Bursa of Fabricius and spleen were also first found to develop at ED 10. While comparing with the prenatal development of lymphoid organs of native chickens with that of previously studied hybrid chickens, the native chickens’ lymphoid organs were found to develop earlier. Taken together with our previous results, the developmental trajectory data of the present study are first to clarify that the immune system of native chickens are being prepared earlier to face the scavenging environment after hatching. Asian J. Med. Biol. Res. December 2017, 3(4): 432-436